Pengaruh Etika Terhadap Niat Melakukan Whistleblowing Dengan Retaliasi Sebagai Variabel Moderating - Rizka Mukhlisiah; Suhairi Suhairi; Nini Syofriyeni (IJAcc, 2020)
This study to examine the effect on the ethical conduct by using the whistleblowing intention retaliation as moderating variable on the employees who work in the office BPKP West Sumatra Province and Inspectorate West Sumatra Province. The data used are primary data by using a questionnaire. The samples using the method of data collection is called purposive sampling, ie employees who work at BPKP West Sumatra Province and employees working in the Inspectorate of West Sumatra Province. The number of samples that can be used as many as 80 respondents. Data were analyzed using analysis techniques PLS (Partial Least Square) through software SmartPLS. The results showed that ethics can not affect the intention do whistleblowing employees BPKP West Sumatra Provincial and Inspectorate West Sumatra Provincial. Furthermore retaliation positive influence on the intention do whistleblowing employees BPKP West Sumatra Provincial and Inspectorate West Sumatra Provincial. The results also show that retaliation can not moderate the intentions of doing ethics whistleblowing employees BPKP West Sumatra and Inspectorate West Sumatra Provincial